2023
DOI: 10.1001/jama.2023.1678
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Stewardship to Prevent Diagnostic Error

Abstract: This Viewpoint discusses the growth of diagnostic stewardship beyond infectious disease to reduce diagnostic errors in other fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Conceptually related to antibiotic stewardship, diagnostic stewardship is focused on improving the use of microbiology laboratory tests to ensure that patients receive correct, timely and pathogen-focused treatment [2] or rather the Right test , for the Right patient , prompting the Right action [3 ▪▪ ]. Appropriate use of diagnostic testing can improve antibiotic use, helping to reduce resistance and improving patient outcomes [1,3 ▪▪ ,4 ▪ ,5 ▪ ]. This review focuses on recently published diagnostic stewardship studies of common clinical infectious syndromes in adults and the impact on antibiotic prescribing and resistance…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually related to antibiotic stewardship, diagnostic stewardship is focused on improving the use of microbiology laboratory tests to ensure that patients receive correct, timely and pathogen-focused treatment [2] or rather the Right test , for the Right patient , prompting the Right action [3 ▪▪ ]. Appropriate use of diagnostic testing can improve antibiotic use, helping to reduce resistance and improving patient outcomes [1,3 ▪▪ ,4 ▪ ,5 ▪ ]. This review focuses on recently published diagnostic stewardship studies of common clinical infectious syndromes in adults and the impact on antibiotic prescribing and resistance…”
Section: Introductionmentioning
confidence: 99%
“…The current randomized clinical trial 7 does add to the discussion about the value of diagnostic tests to inform treatment of common pediatric illnesses. 8 The authors found that antibiotics reduced acute bacterial sinusitis symptom duration for children who tested positive for common nasopharyngeal pathogens. 7 However, nasopharyngeal…”
mentioning
confidence: 99%
“…Broad respiratory pathogen panels have filled this clinical demand, but also demonstrate the limitations of diagnostic testing, especially because a positive test result does not distinguish colonization, infection, or even residual antigenic or genetic material. The current randomized clinical trial does add to the discussion about the value of diagnostic tests to inform treatment of common pediatric illnesses . The authors found that antibiotics reduced acute bacterial sinusitis symptom duration for children who tested positive for common nasopharyngeal pathogens .…”
mentioning
confidence: 99%
“…Reportable health care-associated infection (HAI) metrics that are at least partially based in laboratory reporting have contributed to the development of diagnostic stewardship. 5 Some HAI metrics, such as catheter-associated UTI or Clostridioides difficile infection, have led to a focus on improved testing. Diagnostic stewardship appears to decrease rates of these HAIs by 30% to 60%.…”
mentioning
confidence: 99%
“…Diagnostic stewardship appears to decrease rates of these HAIs by 30% to 60%. 5 It is notable that laboratorybased metrics are some of the few drivers to reduce overtesting and medical overuse. The study by Vaughn et al 4 focused on ASB, which was recently endorsed by the National Quality Forum as a metric of inappropriate diagnosis of UTI in hospitalized patients.…”
mentioning
confidence: 99%